PENGEMBANGAN BAHAN AJAR BERBASIS ETNOMATEMATIKA MASJID RAYA AL- OSMANI UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN DATAR DI KELAS IV SD. - Siti Nurhalizah; Sukmawarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Ethnomathematics is a mathematical study related to culture. In the Malay culture located in Labuhan Deli, there is a historical building, the Al-Osmani Grand Mosque, which contains shapes and motifs that can be associated with mathematics learning and serve as material for developing teaching materials. The objective of this research was to explain the validity, practicality, and effectiveness of the development of ethnomathematics-based teaching materials centered on the Al-Osmani Grand Mosque to enhance the understanding of plane figures in fourth-grade elementary school students. The researcher used the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) to address the issue. The validation stage involved validation by experts (material experts, media experts, and language experts), with feasibility assessments conducted using validation sheets. The trial phase involved 30 students (10 students in the medium group trial and 20 students in the large group trial) and one teacher to assess effectiveness and practicality. Practicality was assessed using teacher and student response questionnaires, while effectiveness was measured through a concept understanding test. The research results indicated that the teaching materials' validity went through two stages: in stage 1, a score of 4.2 was achieved, placing it in the "Good" category, and in stage 2, a score of 4.4 was achieved, placing it in the "Very Good" category. The practicality of the teaching materials received a score of 88%, which is in the "Very Practical" category, and the teacher response questionnaire scored 92% in practicality, also in the "Very Practical" category. The effectiveness of the teaching materials scored 63%. Therefore, the teaching materials can be consivdered valid, effective, and practical.